HUBUNGAN ANTARA EFIKASI DIRI DENGAN REGULASI EMOSI SISWA KELAS IX SMP 15 SEMARANG - Endah Setyoningtyas; Tri Suyati; Farikha Wahyu Lestari (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
This research was motivated by students' lack of emotional control, which caused several problems at SMP 15 Semarang. For example, students feel that they are still doubtful and uncertain about the concept of emotional regulation, students feel that they are lacking in managing, overcoming and expressing emotions. This type of research is quantitative research with an expo facto analysis design. The population of this research was class IX students at SMP 15 Semarang with a total of 265 students. Class IX I with a total of 32 students was used for tryouts. The sample for this research was 4 classes from 8 population classes with a total of 131 students using cluster random sampling technique. The data collection tool used is a research scale in the form of a questionnaire. The results of the research can be concluded as follows: Based on the results of the Spearman Rank correlation test, the sig. (2-tailed) is 0.603 > 0.05, so it can be concluded that there is a significant relationship. With the level of correlation seen from the Correlation Coefficient value of 0.047, which means the level of correlation is moderate.